Value added utilization of by-product electric furnace ferronickel slag as construction materials: A review - Saha, A.; Khan, M.; Sarker, Prabir (Elsevier, 2018)
This paper reviews the potential use of electric furnace ferronickel slag (FNS) as a fine aggregate and binder in Portland cement and geopolymer concretes. It has been reported that the use of FNS as a fine aggregate can improve the strength and durability properties of concrete. Use of some FNS aggregates containing reactive silica may potentially cause alkali-silica reaction (ASR) in Portland cement concrete. However, the inclusion of supplementary cementitious materials (SCM) such as fly ash and blast furnace slag as partial cement replacement can effectively mitigate the ASR expansion. When finely ground FNS is used with cement, it shows pozzolanic reaction, which is similar to that of other common SCMs such as fly ash. Furthermore, 20% FNS powder blended geopolymer showed greater strength and durability properties as compared to 100% fly ash based geopolymers. The utilization of raw FNS in pavement construction is reported as a useful alternative to natural aggregate. Therefore, the use of by-product FNS in the construction industry will be a valuable step to help conservation of natural resources and add sustainability to infrastructures development. This paper presents a comprehensive review of the available results on the effects of FNS in concrete as aggregate and binder, and provides some recommendations for future research in this field.